Pharmacological and Physiological Characterization of the Tremulous Jaw Movement Model of Parkinsonian Tremor: Potential Insights into the Pathophysiology of Tremor - Collins-Praino, Lyndsey E.; Paul, Nicholas E.; Rychalsky, Kristen; Hinman, James R.; Chrobak, James J.; Senatus, Patrick B.; Salamone, John D. (Frontiers in Systems Neuroscience, 2011)
Tremor is a cardinal symptom of parkinsonism, occurring early on in the disease course and affecting more than 70% of patients. Parkinsonian resting tremor occurs in a frequency range of 3-7Hz and can be resistant to available pharmacotherapy. Despite its prevalence, and the significant decrease in quality of life associated with it, the pathophysiology of parkinsonian tremor is poorly understood. The tremulous jaw movement (TJM) model is an extensively validated rodent model of tremor. TJMs are induced by conditions that also lead to parkinsonism in humans (i.e. striatal DA depletion, DA antagonism and cholinomimetic activity) and reversed by several antiparkinsonian drugs (i.e. DA precursors, DA agonists, anticholinergics and adenosine A2A antagonists). TJMs occur in the same 3-7 Hz frequency range seen in parkinsonian resting tremor, a range distinct from that of dyskinesia (1-2 Hz) and postural tremor (8-14 Hz). Overall, these drug-induced TJMs share many characteristics with human parkinsonian tremor, but do not closely resemble tardive dyskinesia. The current review discusses recent advances in the validation of the tremulous jaw movement model, and illustrates how this model is being used to develop novel therapeutic strategies, both surgical and pharmacological, for the treatment of parkinsonian resting tremor.